Modulation of Skin Extracellular Matrix and Collagen Homeostasis: Differential Effects of Aerobic and Resistance Training on Skin Aging - Brodowska, Anna; Kuś, Justyna; Białowąs, Patrycja; Zięba, Natalia; Czapiński, Olgierd; Tomicka, Ewa; Knapik, Anna; Stadnicka, Olga; Ciesielski, Maciej; Pysiewicz, Mateusz (Quality in Sport, 2026)
Background. The structural integrity of the skin relies on the extracellular matrix (ECM) and collagen homeostasis, which degrade during aging. While physical activity is a systemic regulator of cutaneous homeostasis, the molecular divergence between distinct training modalities remains poorly characterized. Specifically, the pathways through which aerobic training (AT) versus resistance training (RT) influence skin health require elucidation. Aim. To analyze the molecular mechanisms through which physical activity influences skin aging, focusing on ECM remodeling, skin density, and counteracting aging processes. Material and methods. A narrative review of literature from the last decade was conducted, focusing on mechanotransduction, myokine signaling, and fibroblast gene expression under the influence of AT and RT. Results. RT induces skin thickening by activating mechanotransduction pathways and stimulating structural genes like biglycan (BGN), HAS2, and CHSY1. This process is supported by the suppression of circulating plasma inhibitors such as CXCL4. Simultaneously, AT serves as a systemic antioxidant filter. By reducing senescence - associated secretory phenotype (SASP) markers and inhibiting matrix metalloproteinase (MMPs) activity, AT creates a protective environment that prevents the degradation of newly synthesized collagen fibers. Conclusions. A hybrid training model (combining AT and RT) represents the most effective non - pharmacological strategy for skin rejuvenation. Such a dual - pathway approach stimulates the production of structural components and stabilizes the dermal environment against metabolic and oxidative stress. The integration of physical activity into anti - aging protocols offers a biological "reprogramming" of the skin, leading to improved structural integrity and resilience.